Study of Outcome of Severe Head Injury Using Glasgow Coma Scale-Pupil (GCS-P) Score- A Hospital Based Cross-Sectional Study - KC, Raj Kumar; Thapa, Diwas; Shrestha, Sanjay; Chaudhary, Sudip; Gautam, Nischal (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Traumatic brain injuries are typically characterized as disruptions in brain function or evidence of brain pathology resulting from external forces. Given the signiﬁcant mortality associated with traumatic brain injury, this study aimed to evaluate the applicability of the Glasgow Coma Scale-Pupil score in outcome of severe head injury patients. MATERIAL AND METHODS A prospective observational study was conducted at Neurosurgery Department at UCMS, Bhairahawa, Nepal from October, 2021 to March, 2023 (18 months). All the patients presenting in the emergency department with severe traumatic brain injury i.e., Glasgow Coma Scale score 3 to 8 were enrolled in the study after obtaining written consent from parents. RESULTS Out of 92 patients , 79 were male and 13 were female. The average age was 37.88 ± 16.06 years with most of the patients being from the age groups 31-40 years (25%). The results showed that about 83.8% mortality was found in both pupils non-reactive followed by 66.7% mortality in groups with one pupil unreactive and 61.8% mortality in both reactive pupils.The results showed an overall mortality of 71.7%. Among 28.3% of surviving patients, 57.69% patients had unfavorable outcomes and 42.31% patients had favorable outcomes. The receiver operating characteristic curve showed that the Glasgow Coma Scale-Pupil score is better than the Glasgow Coma Scale in predicting unfavorable outcomes of patients with an Area under the curve of 0.807 to 0.689. CONCLUSION The decline in the Glasgow Coma Scale-pupil score was associated with increased mortality and the additional two points in the Glasgow Coma Scale-pupil score gives more idea about the prognosis. Glasgow Coma Scale-pupil score is comparable to Glasgow Coma Scale for predicting mortality but better for predicting unfavorable outcomes in severe head injury patients.